Fluid restriction negatively affects energy intake and growth in very low birthweight infants with haemodynamically significant patent ductus arteriosus. (23rd May 2019) - Hansson, Lena; Lind, Torbjörn; Wiklund, Urban; Öhlund, Inger; Rydberg, Annika
Abstract: Aim: We explored if fluid restriction in very low birthweight (VLBW) infants with a haemodynamically significant patent ductus arteriosus (PDA) affected energy and protein intakes and growth. Methods: Retrospectively, we identified 90 VLBW infants that were admitted to Umea University Hospital, Sweden, between 2009 and 2012: 42 with and 48 without haemodynamically significant PDA (hsPDA). Anthropometric, fluid, energy and protein intake data during the first 28 days of life were expressed as z‐scores. Results: In the 42 infants diagnosed with hsPDA, fluid intake was restricted after diagnosis, resulting in a decrease in energy and protein intake. No decrease was observed in the other 48 infants in the cohort. Multivariate analysis showed that the z‐score of weight change depended on both ductus arteriosus status and energy intake; thus, infants with hsPDA did not grow as expected with the energy provided to them. Conclusion: Energy and protein intake was diminished in prematurely born infants with hsPDA when fluid was restricted after diagnosis. The initial reduction in intakes may have contributed to the lower postnatal growth observed in these infants.